Integrative Approach for the Reliable Detection and Specific Identification of the Microsporidium Loma morhua in Atlantic Cod (Gadus morhua). (13th July 2016) - Frenette, Aaron P.; Eydal, Matthías; Hansen, Haakon; Burt, Michael D.B.; Duffy, Michael S.
Abstract: Microsporidia are fungal parasites that infect diverse invertebrate and vertebrate hosts. Finfish aquaculture supports epizootics due to high host density and the high biotic potential of these parasites. Reliable methods for parasite detection and identification are a necessary precursor to empirical assessment of strategies to mitigate the effects of these pathogens during aquaculture. We developed an integrative approach to detect and identify Loma morhua infecting Atlantic cod. We show that the spleen is more reliable than the commonly presumed gills as best organ for parasite detection in spite of substantial morphological plasticity in xenoma complexes. We developed rDNA primers with 100% sensitivity in detecting L. morhua and with utility in distinguishing some congeneric Loma species. ITS sequencing is necessary to distinguish L. morhua from other congeneric microsporidia due to intraspecific nucleotide variation. 64% of L .  morhua ITS variants from Atlantic cod have a 9‐nucleotide motif that distinguishes it from Loma spp. infecting non‐ Gadus hosts. The remaining 36% of ITS variants from Atlantic cod are distinguished from currently represented Loma spp., particularly those infecting Gadus hosts, based on a 14‐nucleotide motif. This research approach is amenable to developing templates in support of reliable detection and identification of other microsporidian parasites in fishes.